Methodological aspects of critical theories in knowledge organization - Martnez-Ávila, Daniel [UNESP]; Semidáo, Rafael [UNESP]; Ferreira, Marcio [UNESP] (My University, 2016)
This paper focuses on the methodological configuration of critical theories in the knowledge organization domain. We present these critical theories as a response to the ethical problems that affect particular groups in universal classification systems. We analyze the epistemological stances and methodological implications of three instances of critical theories applied to knowledge organization. As a result, we present a frame-work of methodological dynamics composed of three steps: 1) aporelkr, 2) theoretical framework; and 3) proposition. We conclude that certain epistemologies (such as pragmatism) present a more developed methodology according to this framework.
Keywords: Classification; Critical theories; Knowledge organization; Methodological aspects; Universal systems